Cocinar y castigar: Recetario de torturas en Cocinando con Elisa de Lucía Laragione - Morales, Maybel Mesa (Latin American Theatre Review, 2018)
This article explores spatial dimensions in Lucía Laragione´s work Cocinando con Elisa (1993) and the way in which processes of representation of historical memory are inscribed as social reconfiguration. The point of departure is the theoretical framework that analyzes the language of spatial relationships as one of the fundamental means of interpreting reality (Lotman), pointing to the connections between space, power, and memory, as well as to the impact of their confrontation in the performative context of the play. In this study, the telos of torture is assumed as an alienated act of identity construction. Cocinando con Elisa is part of the corpus of Argentine dramaturgy that interprets torture in a symbolico-allegorical way as the essence of the domination device of Argentine dictatorship over the female body.